The role of sports in improving the lifestyle of university students - Salman, Aayad; Abdulsada , Aswar (Journal of Physical Education, 2025)
This research aims to clarify the importance of practicing sports and its role in improving the lifestyle of university students. By understanding how sports contribute to strengthening social relationships within the academic community and enhancing the physical and mental health of university students, sports have become an effective tool in the modern era. They are not limited to entertainment or amusement but also contribute to building the character of university students, enhancing their interactive abilities, and instilling moral values such as cooperation, tolerance, and discipline. The study highlights the historical background of sports, starting from the civilizations of the Mesopotamian Valley, thru the Islamic civilization, up to the modern era, where it has become a means to enhance national belonging and combat deviant behaviors. The research seeks to propose practical mechanisms to activate sports activities, given their fundamental role in enhancing the lives of university youth on physical, psychological, and social levels. The study relied on the descriptive analytical method, where the questionnaire was distributed to 200 male and female students from different colleges at the University of Baghdad and Al-Mustansiriya University. The results showed that practicing sports positively contributes to the development of social skills such as cooperation, communication, and building friendships. And it improves mental and physical health. Accordingly, the research recommends increasing support for university sports activities to enhance the lifestyle of university students.